Carbon Nanomaterials: Unique Tube–Ring Interactions: Complexation of Single‐Walled Carbon Nanotubes with Cycloparaphenyleneacetylenes (Small 26/2018). Issue 26 (27th June 2018) - Miki, Koji; Saiki, Kenzo; Umeyama, Tomokazu; Baek, Jinseok; Noda, Takeru; Imahori, Hiroshi; Sato, Yuta; Suenaga, Kazu; Ohe, Kouichi
Abstract : In article number1800720, Koji Miki, Kouichi Ohe, and co‐workers report the "ring toss" method, throwing carbon nanorings onto carbon nanotubes, to prepare "tube‐in‐ring" supramolecular complexes. Carbon nanorings, [n]cycloparaphenyleneacetylenes, are utilized to demonstrate the formation of "tube‐in‐ring" complexes. The good size fit between the concave inner surface of the carbon nanorings and the convex outer surface of carbon nanotubes is important for the efficient production of rotaxane‐like complexes. This work provides a strategy to prepare interlocked carbon nanotubes for next‐generation electric devices and theranostic agents.